Group Counseling With Positive Reinforcement Techniques To Improve Learning Discipline - Durrotunnisa Durrotunnisa; Santinovita Cristin (Universitas Pendidikan Ganesha, 2023)
The main problem in this study is the low discipline of student learning related to attendance at school, doing assignments, participating in lessons, and disobedience to the rules. The purpose of this research is to improve student learning discipline. Hypothesis testing was carried out by statistical analysis using the Mann Whitney formula at a significant level (0.05). The results of the descriptive analysis showed that the level of student learning discipline before and after participating in positive reinforcement technique group counseling activities included 4 students having a low level of learning discipline and 4 students having moderate learning discipline. The level of student learning discipline after participating in group counseling services with positive reinforcement techniques increased more than before attending services. The results showed that group counseling services with positive reinforcement techniques were effective in increasing student learning discipline.